2009
DOI: 10.1080/10641950802601161
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Uterine Artery Doppler Anomalies in Patients with Preeclampsia

Abstract: In patients with preeclampsia, the presence of uterine artery Doppler anomalies (high resistance index with or without bilateral notches) was associated with unfavorable pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Doppler fluxometry applied to the uterine arteries allowed the confirmation of the hemodynamic disturbances underlying placental insufficiency, and demonstrated that in PE occurs an increased (circulatory) resistance of placental vascular territory (Papageorghiou & Leslie, 2007;Boukerrou et al, 2009). As changes in placental blood flow are observed in PE before the onset of symptoms (Papageorghiou & Leslie, 2007), uterine artery Doppler, is performed early in the second trimester of pregnancy, in order to predict PE.…”
Section: Etiology and Pathophysiology Of Preeclampsiamentioning
confidence: 99%
“…Doppler fluxometry applied to the uterine arteries allowed the confirmation of the hemodynamic disturbances underlying placental insufficiency, and demonstrated that in PE occurs an increased (circulatory) resistance of placental vascular territory (Papageorghiou & Leslie, 2007;Boukerrou et al, 2009). As changes in placental blood flow are observed in PE before the onset of symptoms (Papageorghiou & Leslie, 2007), uterine artery Doppler, is performed early in the second trimester of pregnancy, in order to predict PE.…”
Section: Etiology and Pathophysiology Of Preeclampsiamentioning
confidence: 99%